EDUCATIONAL ENVIRONMENT AS A FUNDAMENTAL CONDITION FOR THE DEVELOPMENT OF UNIVERSITY TEACHERS' METHODICAL COMPETENCE - Olga A. Sotnikova; Olga A. Volkova (Высшее образование в России)
The article discusses the principle of formation of universal and specific components of methodical competence of university teachers through the functioning of the various levels of educational environment as organizational culture of the University. This principle relates reflective, need and motivational, structural, technological, cognitive and constructive components of the methodical competence with the levels of development of organizational culture of the University. Specific educational environment, viewed from the perspective of cut-through teacher training, contributes to the development of methodical competence of a university teacher.